2023
DOI: 10.31729/jnma.8095
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Medications Use among Chronic Hemodialysis Patients Visiting the Outpatient Department of Nephrology of a Tertiary Care Centre: A Descriptive Cross-sectional Study

Abstract: Introduction: Anti-hypertensive medications are prescribed for the management of high blood pressure which is the leading cause of mortality in chronic hemodialysis patients. The objective of our study was to find out the prevalence of anti-hypertensive medication use among chronic hemodialysis patients visiting the outpatient Department of Nephrology of a tertiary care centre. Methods: This was a descriptive cross-sectional study conducted among chronic hemodialysis patients visiting the Department of Nephrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Increased cytokine expression in the circulation is characteristic of most patients undergoing ECMO treatment, as respiratory failure is often accompanied by inflammatory conditions, such as pneumonia or sepsis during acute respiratory distress syndrome (ARDS) [13, 14]. ECMO is often used as a treatment for chronic obstructive pulmonary disease (COPD), which is characterized by inflammation [15, 16]. Additionally, it has been reported that ECMO treatment can induce systemic inflammatory response syndrome (SIRS), which leads to increased mortality [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…Increased cytokine expression in the circulation is characteristic of most patients undergoing ECMO treatment, as respiratory failure is often accompanied by inflammatory conditions, such as pneumonia or sepsis during acute respiratory distress syndrome (ARDS) [13, 14]. ECMO is often used as a treatment for chronic obstructive pulmonary disease (COPD), which is characterized by inflammation [15, 16]. Additionally, it has been reported that ECMO treatment can induce systemic inflammatory response syndrome (SIRS), which leads to increased mortality [17, 18].…”
Section: Introductionmentioning
confidence: 99%